Reguły gry = The rules of the game - Tosik, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Defined as a game of an author with a reader, detective fiction reveals its dualistic character - of a puzzle to be solved or as a structure describing the investigation and the reconstruction of the murder at the same time. As an interactive game, detective fiction undergoes constant changes in order to redefine the rules of the game and surprise the reader. The author of the article comes to a conclusion that a present tendency to widen the social setting in crime fiction leads to making it a new element in the game with the reader.
Keywords: powieść kryminalna; literatura polska - 20 w. - tematyka